Sukaustytosios ir spalvingosios bibliotekos įvaizdis Lietuvos knygos muziejuje - Pacevičius, Arvydas (Knygotyra, 2003)
The exposition of the spread and functioning of the book in society should occupy a significant place in the future book museum. It is obvious that this part of the book cycle is best represented by the library (institutional or personal), and more precisely – the whole library world and its interaction with the book, which is sometimes intangible. This requires consideration how to represent the material on the library history or, in other words, create an image of the library. The article defines the identity of the library as a museum object and shows its place in the framework of the future Book Museum of Lithuania. The image of chained library, which became stereotypical in virtual space of Internet, is shaped on a base of cases of chained books in the Cathedral Library and Dominican Monastery Library that were both located in Vilnius. The technique of book binding and the colors of the book collection are disclosed by analysis of description of libraries in ancient inventories and catalogues of the Grand Duchy of Lithuania. One can draw a conclusion that the functions of chained library and the representation of color collection remind the modern exposition of the museum. The historical image of the library must become an integrated part of the Lithuanian Book Museum.